997. Protection of Unvaccinated Individuals by Influenza Vaccine Coverage of Household Contacts. (26th November 2018) - Malosh, Ryan E; Evans, Richard; Martin, Emily T; Petrie, Joshua G; Monto, Arnold S
Abstract: Background: The evidence that influenza vaccination programs provide some protection to unvaccinated members of a community (i.e., indirect effects) is lacking. We sought to determine the indirect effects of influenza vaccine in prospective cohort study of households with children. Methods: We used longitudinal data over six influenza seasons from the Household Influenza Vaccine Evaluation (HIVE) study. We categorized households each season based on the proportion of members who received a seasonal influenza vaccination: unvaccinated (0%), low coverage (1–50%), moderate coverage (50–99%), and fully vaccinated (100%). We used mixed-effect Poisson regression models adjusted for age group and sex with random effects to account for household clustering and repeated measures. We estimated the association between the proportion of vaccinated household members and the incidence of influenza virus infection in the entire cohort. We then estimated the indirect effects of influenza vaccination by comparing unvaccinated members of households with low levels of vaccination to unvaccinated members of households with higher levels of vaccination. Results: During 7, 286 person-seasons of follow-up, we detected 578 cases (8 per 100/season) of influenza virus infection. The seasonal incidence rate was highest in completely unvaccinated households (10 per 100/seasons) and lower at all other levels of vaccine coverage (Figure 1). Individuals in fully vaccinated households had a 29% lower seasonal incidence rate of influenza infection compare to those in unvaccinated households (IRR 0.72, 95% CI 0.56–0.93). The estimated indirect VE comparing unvaccinated individuals in completely unvaccinated households to those in households with moderate vaccine coverage was 40 % (95% CI −4 to 65). Conclusion: We demonstrate that vaccination of close contacts can reduce incidence of influenza in unvaccinated members of a community. Despite insufficient evidence, guidance from public health authorities currently suggests that vaccination protects close contacts. Our findings quantifying the protective effects of seasonal influenza vaccination of household contacts in unvaccinated individuals can provide clearer evidence for global vaccine recommendations. Disclosures: All authors: No reported disclosures.